2023
DOI: 10.1001/jamanetworkopen.2023.14428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P2Y12 Inhibitors on Organ Support–Free Survival in Critically Ill Patients Hospitalized for COVID-19

Abstract: ImportancePlatelet activation is a potential therapeutic target in patients with COVID-19.ObjectiveTo evaluate the effect of P2Y12 inhibition among critically ill patients hospitalized for COVID-19.Design, Setting, and ParticipantsThis international, open-label, adaptive platform, 1:1 randomized clinical trial included critically ill (requiring intensive care–level support) patients hospitalized with COVID-19. Patients were enrolled between February 26, 2021, through June 22, 2022. Enrollment was discontinued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Adaptive trial design has been successfully used in the critically ill to test COVID-19 therapies [ 78 – 83 ]. The MATIC-2 trauma trial (NCT06070350) makes use of an adaptive platform design to compare whole blood to component therapy, and TXA to placebo in children with traumatic bleeding.…”
Section: Implementing Use Of Biomarkers and Phenotypes: Improving Tra...mentioning
confidence: 99%
“…Adaptive trial design has been successfully used in the critically ill to test COVID-19 therapies [ 78 – 83 ]. The MATIC-2 trauma trial (NCT06070350) makes use of an adaptive platform design to compare whole blood to component therapy, and TXA to placebo in children with traumatic bleeding.…”
Section: Implementing Use Of Biomarkers and Phenotypes: Improving Tra...mentioning
confidence: 99%
“…A total of 25 studies 11 13 , 15 19 , 22 , 26 41 involving, 17 911 patients were included. There were 18 studies comparing different doses of anticoagulants on hospitalized patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, recently, several randomized controlled trials (RCTs) have shown that intermediate and therapeutic doses are associated with lower thromboembolism risk 11 , 12 . Secondly, regarding the need for additional antiplatelet therapy in critically ill patients, many studies suggest that adding antiplatelet treatment on top of prophylactic anticoagulation does not provide additional benefits 11 , 13 . However, a meta-analysis incorporating retrospective studies suggests that antiplatelet therapy can improve clinical outcomes 14 .…”
Section: Introductionmentioning
confidence: 99%
“…P2Y12 inhibitors could reduce the incidence and in-hospital mortality of Staphylococcus aureus bacteremia [ 11 , 18 ]. Unlike bacterial infections, P2Y12 inhibitors appear to be ineffective against infections with viruses [ 19 ]. Under the sepsis-3 criterion, to the best of our knowledge, the present study is the first to assess the impact of P2Y12 inhibitors on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%